THE IMPORTANCE OF USING ORGANIC BINDERS IN OBTAINING BRICKETS - Nasiba Vokhidova (Web of Journals Publishing, 2025)
This work examines organic binders—specifically coal tars modified with mechanically activated organo-mineral additives—for producing durable fuel briquettes from low-grade brown-coal waste. The binder systems were prepared by mechanically activating mineral components (e.g., ash/slag fines, clayey fractions) and blending them with tar to enhance adhesion, plasticity, and curing. Brown-coal powders from mountain deposits were briquetted under moderate pressure and ambient curing. Performance was assessed by cold compressive strength, drop resistance, abrasion loss, water uptake, ash content, and lower heating value. The modified organic binders yielded briquettes with improved mechanical integrity and moisture resistance compared with tar-only controls, while maintaining acceptable combustion characteristics. Mechanical activation of the organo-mineral fraction reduced binder dosage needed for target strengths, enabling higher coal content and better energy density. Overall, organic binders reinforced with activated mineral phases offer a practical, lower-cost route to valorize brown-coal waste into transportable, storable, and efficiently combustible briquettes.
Keywords: Brown coal; coal tar binder; organo-mineral additive; mechanical activation; fuel briquette; ash content; heating value; moisture resistance; compressive strength.